STUDY ON GENOTOXIC EFFECTS OF METRONIDAZOLE AND TINIDAZOLE IN ALBINO MICE - DR SHREENIVAS P. REVANKAR (International Journal of Pharma and Bio Sciences, 2013)
The present study was planned to explore and compare the Genotoxic potential of metronidazole and tinidazole in Swiss albino mice. Genotoxicity testing was carried out using single cell gel electrophoresis (comet assay) and micronuclei assay. In acute study only single dose was given and in sub acute study, doses were repeated for 7 days. Blood sample was collected by retro orbital puncture and bone marrow was collected from femur after sacrificing the animal. Blood sample was used for comet assay and bone marrow sample for micronuclei assay. Increase in comet tail length and percentage of micro nucleated polychromatic erythrocytes (% MnPCE) was observed in groups treated with single and multiple doses of Cyclophosphamide. The same effect was seen to some extent metronidazole whereas tinidazole did not show any significant changes.The results indicate that metronidazole showed mild Genotoxic effect while tinidazole was devoid of genotoxicity.